2011
DOI: 10.1017/s1355617711001469
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Oxygen Desaturation and Disordered Sleep as a Potential Factor in Executive Dysfunction in Sickle Cell Anemia

Abstract: Previous research has identified cognitive impairment in children with sickle cell anemia (SCA, Hemoglobin SS) compared with controls, partly accounted for by overt neuropathology after clinical stroke, “covert” (“silent”) infarction, and severity of anemia. However, cognitive deficits have also been identified in children with SCA with no history of stroke and a normal T2-weighted magnetic resonance imaging (MRI) scan. Our aim was to investigate whether nocturnal hemoglobin oxygen desaturation and sleep fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…Several studies have shown that nocturnal hypoxemia is associated with higher morbidity in SCD manifesting as higher degree of anemia and lower cumulative annual average hemoglobin levels [24,25], increased pulmonary artery pressures [26], worse pulmonary function tests [25], increased left ventricular (LV) hypertrophy and LV diastolic dysfunction [27], increased incidence of priapism [28], and nocturnal enuresis [29], more frequent painful [30] and vaso-occlusive crises in general, increased incidence of CNS events [31], worse executive cognitive function [32] and even vitamin C deficiency, suggestive of reduced anti-oxidant capacity [33].…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that nocturnal hypoxemia is associated with higher morbidity in SCD manifesting as higher degree of anemia and lower cumulative annual average hemoglobin levels [24,25], increased pulmonary artery pressures [26], worse pulmonary function tests [25], increased left ventricular (LV) hypertrophy and LV diastolic dysfunction [27], increased incidence of priapism [28], and nocturnal enuresis [29], more frequent painful [30] and vaso-occlusive crises in general, increased incidence of CNS events [31], worse executive cognitive function [32] and even vitamin C deficiency, suggestive of reduced anti-oxidant capacity [33].…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
“…Nighttime hypoxemia and increased arousals have been also associated with worse executive function [32,151].…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…8,9 The risk of tissue injury is also increased by chronic anemia 1 and low daytime and nocturnal oxygen saturation. 10,11 Low oxygen saturation has been linked not only to lower IQ 12 and poorer performance on executive function tasks 13 in SCA but also has been reported in children with obstructive sleep apnea experiencing similar nocturnal oxygen desaturation. 14 The disruption to breathing, and subsequent oxygen desaturation, has been shown to interfere with synaptic plasticity and consequently various cognitive functions.…”
mentioning
confidence: 99%
“…Severely anaemic patients (i.e. haematocrit <20%) have shown poorer performance on both verbal and performance aspects of IQ [119], and have accounted for a significant proportion of variance in FSIQ [64,138] and executive functions [64].Low nocturnal peripheral oxygen saturation was associated with reduced performance on the Tower of London test, which measures strategic planning and rule learning [139]. In the baseline data from the Silent Infarct Trial, a 1% reduction in daytime oxygen saturation was associated with a reduction in 0.75 full scale IQ points [122].…”
Section: Non-imaging Biomarkers Of Functionmentioning
confidence: 98%